KESESUAIAN PEMANFAATAN RUANG DAN DAMPAK KONVERSI MANGROVE TERHADAP PERUBAHAN KUALITAS PERAIRAN DI MUARA DESA BAGAN DELI KECAMATAN MEDAN BELAWAN - Tawakal Kusuma; Darma Bakti; Rusdi Leidonald (AQUACOASTMARINE, 2016)
The spatial planning is important to build a region in order to be a suistinable development. Thedeviation of space utilization which inappropriate with the spatial planning of local government willcause water quality degradation. Bagan Deli Village is a settlement with commonly high inhabitant, sothere has been deviation of space utilization, which cause degradation water quality by domesticpollution and loss of mangrove function as pollution controller. The aim of this research was toobserved deviation of space utilization in Bagan deli Village and impact of mangrove deforestationtoward water quality. it was held on March 2016 till May 2016. Water sampling done using purposivesampling method. Secondary data obtained from department of spatial and building such as MedanBelawan spatial planning map. From this research known there has been deviation of space utilizationsuch as irregulation use of river border and mangrove deforestation which has broke law 26 of 2007,law 1 of 2014 and local government regulation No. 13 of 2011, in addition there has been degradationof water quality became lightly polluted based on US-EPA (Environmental Protection Agency)calculation compared with water quality standard class III in ministerial decree No. 115 of 2003Keywords : Spatial plans, mangrove deforestation, water quality